The Effect of Dumbell Load Training on Straight Block Speed on Muay Thai Athletes Unsyiah Banda Aceh - Rahmat, Zikrur; Irfandi, Irfandi; Munzir, Munzir (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2022)
Based on the results of observations at UKM Unsyiah, not all athletes from UKM Muay Thai Unsyiah can hit